Basic Profile of Child Marriage in Chad - Malé, Chata; Wodon, Quentin (World Bank, Washington, DC, 2016)
This brief has provided a basic profile of child marriage in Chad. Measures of child marriage are very high. The share of women ages 18-22 who married as children is 68.7 percent and it has not declined substantially over time. The share of girls marrying very early, before the age of 15, has declined slightly. Child marriage is associated with lower wealth, lower education levels, and higher labor force participation. These are however only correlations, not necessarily causal effects. Other briefs in this series look at potential causal effects.